USING RICE BRAN FOR FUNCTIONAL PURPOSE BREAD PRODUCTION TECHNOLOGY - Boldina A.A.; Sokol N.V.; Sanzharovskaya N.S. (Техника и технология пищевых производств)
The article reveals the results of a number of studies aimed at improving the functional purpose bread production technology using rice bran. The purpose of the research was to study the influence of rice bran on the nutritional value of baked goods based on the final product quality and nutritional value assessment. The authors had been using general and specific analytical methods during the experiments. The results were processed with Statisticasoftware for Windows. The authors suggested to use rice bran as an enriching ingredient for bread made of wheat flour. The results show that introduction of rice bran into the dough has a significant effect on bread quality. The research revealed that the best proportion is 15% to the weight of flour. It allows to obtain a product with high organoleptic and physicochemical properties. The authors developed a recipe for bread «Mechta» with increased content of potassium, calcium, phosphorus and iron. They proved that this new type of bread that includes rice bran has higher biological value compared with the control sample produced without an additive. The safety criteria of bread «Mechta» fully comply with the established requirements of TR TS 021/2011. The results obtained during the research allowed to conclude that rice flour can be used in functional purpose bread production technology.